Creation of Pentatonic Etude 1 as Teaching Material Development for Solfeggio Course (Current Research in Education: Conference Series Journal, 2024)
Solfeggio is one of the basic subjects that must be mastered by students enrolled in music education programs. Through solfeggio courses, students are equipped with basic competencies in the form of the ability to hear, feel, play, read, and write both melodic and rhythmic notation. Over the past three years, students' abilities have declined. The most drastic decline occurred among the class of 2022, resulting in many students failing the solfeggio course. Some students struggled to keep up with the material presented. This problem prompted researchers to develop teaching materials by creating pentatonic etude 1 because the materials taught so far have been limited to the use of diatonic scales. The creation of works used as teaching materials is very important to help overcome students' difficulties in learning solfeggio. The research was conducted in several stages, including situation analysis, data collection, artistic work, work testing, and application of the work into lecture teaching materials. The research method used was practice-led research. The results of the study show that pentatonic etude 1 is a development of teaching materials for solfeggio courses that can help students master the pentatonic scale.